Preparation and characterization of multilayer anti-reflective coatings via sol-gel process. Issue 3 (15th February 2018) - Kesmez, Ömer; Akarsu, Esin; Çamurlu, H. Erdem; Yavuz, Emre; Akarsu, Murat; Arpaç, Ertuğrul
Abstract: Single layer and multilayer films consisting of SnO2, Ta2 O5, SiO2, TiO2, indium tin oxide (ITO) and antimony tin oxide (ATO) have been prepared by sol-gel dip coating technique. All of the multilayer films contained a SiO2 top layer, which was composed of SiO2 nanoparticles. The other films had polymeric character. Obtained films were characterized by ellipsometry, XRD, AFM and SEM. Light transmittance values of the films were compared. Films other than SiO2 and Ta2 O5 were found to have crystalline structure. Thickness values of the films were in the range of 30–115 nm and roughness values were in 1.2–23 nm range. Single layer porous silica provided 95% light transmittance, whereas ITO-TiO2 -SiO2 multilayer film provided a light transmittance of 97.2%.